A physiotherapy service to an emergency extended care unit does not decrease admission rates to hospital: a randomised trial. Issue 8 (6th September 2011) - Jesudason, Christabel; Stiller, Kathy; McInnes, Matthew; Sullivan, Thomas
Abstract : Background: One of the reasons physiotherapy services are provided to emergency departments (EDs) and emergency extended care units (EECUs) is to review patients' mobility to ensure they are safe to be discharged home. Aim: To investigate whether a physiotherapy service to an EECU altered the rate of hospital admission, rate of re-presentation to the ED, visits to community healthcare practitioners, return to usual work/home/leisure activities and patient satisfaction. Methods: A randomised trial with concealed allocation, assessor blinding and intention-to-treat analysis was undertaken in an EECU. The sample comprised 186 patients (mean age 70 years, 123 (66%) female patients, 130 (70%) trauma) who were referred for physiotherapy assessment/intervention. Referral occurred at any stage of the patients' EECU admission. All participants received medical/nursing care as required. The physiotherapy group also received physiotherapy assessment/intervention. Results: The physiotherapy group had a 4% (95% CI −18% to 9%) lower rate of admission to hospital than the control group and a 4% (95% CI −6% to 13%) higher rate of re-presentation to the ED, which were statistically non-significant (p≥0.45). Differences between groups for use of community healthcare resources, return to usual work/home/leisure activities and satisfaction with their EECU care were small and not significant. Conclusion: A physiotherapy service for EECU patients, as provided in this study, did not reduce the rate of hospital admission, rate of re-presentation to the ED, use of community healthcare resources, or improve the rate of return to usual work/home/leisure activities or patient satisfaction. Trial registration number: ANZCTRN12609000106235.